MOTORWAYS OF THE SEA: MYTH O REALITY? - Mikusova, Miroslava (Doprava a spoje, 2009)
This paper explains the concept of the Motorways of the Sea as a powerful tool to increase the competitiveness of maritime transport. It presents the basic conditions for its successful implementation into navigation reality. It also pointes to the questions which should be urgently responded to make the Motorways of the Sea reality.